Cytological dilemma of a rare subcutaneous fungal infection: Phaeoacremonium griseorubrum (Indian Journal of Case Reports, 2018)
Human disease caused by Phaeoacremonium species is rare. It was first reported in 1974 to cause subcutaneous tissue infection in the renal transplant recipient. Since then, only a few cases have been reported in the literature; however, underreporting is common in such cases due to incomplete or incorrect identification. Furthermore, some cases of subcutaneous infection in otherwise healthy patients may be asymptomatic and definitive identification of the etiological agent is not pursued. Identification of fungi at the species level is challenging by conventional methods; hence, final identification of fungi is based on culture. Phaeoacremonium has a very wide spectrum of presentation ranging from subcutaneous infections to fungemia and disseminated disease. We report a case of subcutaneous tissue swelling in an immunocompetent 55-year-old male, in whom etiology was traced to Phaeoacremonium griseorubrum. To the best of our knowledge, this report of P. griseorubrum causing human infection is second of its kind and the first from India. The patient did not respond well to oral itraconazole therapy and was advised surgical debridement with amphotericin B therapy.